Surgical Management of a Giant Adrenal Pseudocyst: A Case Report and Review of the Literature in the Last Decade. (1st February 2018) - Paramythiotis, Daniel; Bangeas, Petros; Karakatsanis, Anestis; Goulas, Patroklos; Nikolaou, Irini; Rafailidis, Vasileios; Kouskouras, Konstantinos; Papadopoulos, Vasileios; Lypiridou, Sofia; Karayannopoulou, Georgia; Michalopoulos, Antonios
Abstract : Adrenal pseudocysts are rare entities and occurred in the 5th and the 6th decades of life. They are discovered accidentally, while appearing with nonspecific clinical and imaging findings. We report a case of a 28-year-old woman presented in our Emergency Department complaining about upper abdomen pain. Computed tomography revealed a hypodense cystic lesion containing hyperdense material. The size of a mass was 11. 7 × 9.3 × 6.6 cm in diameter close to the pancreas, but the origin was from the left adrenal gland. The mass was excised with surgical laparotomy. Giant adrenal pseudocysts are rare entities. Final diagnosis usually confirmed with the pathology examination. Management of such adrenal lesions depends on the unique characteristics, the surgeon's experience, and local resources.